PENGARUH PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN DI UNIT TATA GRAHA HOTEL MENARA PENINSULA - Taviprawati, Ervina; Sembiring, Vienna Artina (Jurnal Ilmiah Pariwisata, 2019)
Hospitality as a part of the tourism industry is growing rapidly as well. In hotels already operating as well as the development of tourism, sometimes the guest still complaints. Especially in a hotel that is not managed professionally and efficiently, there will be many problems encountered for guest. However, the hotel strives to minimize the complaint. This is done so that guest feel satisfied with the services provided, it is expected to be regular guest. It is very clear that every company must pay attention to the quality of its employees. Quality can be achieved if through employee development. Development can be through education and training. One of them is through career development. This research was conducted to find out how much influence the development of careers on employee performance in Housekeeping Unit at Menara Peninsula Hotel. The research method was conducted by descriptive and correlational (correlation research), using purposive sampling method with 22 respondents, they are employees of the Menara Peninsula hotel. The results obtained that there is a strong positive relationship between career development variables and employee performance in the Tatagraha Hotel Unit, Menara Peninsula. This shows that career development variables affect employee performance, meaning that career development variables can influence performance variables very strongly. While the performance variable is influenced by other factors not examined.